A highly tunable and angle-insensitive plasmon resonances based on graphene ring-circle arrays. (8th August 2018) - Zeng, Zhiyong; Chen, Xingyu; Liu, Jiangwei
Abstract: In our work, we propose a highly tunable and angle-insensitive plasmon resonances based on graphene ring-circle arrays. This was done by putting a layer of silica insulation material on the bottom layer of graphene ring-circle. Through simulation using finite difference time domain method (FDTD), it is found that a high sensitivity and low sensing medium refractive index n med can be achieved. By changing the doping level n g and the Fermi level E F, we can find the graphene ring-circle arrays sensor has a good tunability. In addition, the simulation results indicate that the sensor of the graphene ring-circle has a good angle polarization tolerance and remarkable tunable performance. Therefore, the introduction of graphene ring-circle into sensor can strengthen the absorption of biological molecules and effectively detect the sensing range. Thus, it can be easily used to detect possible refractive index changes in gases, liquids and mixed solutions by the graphene ring-circle sensor. There will be more wide application prospects in the fields of biosensing, detection and imaging.